Peran Transformasi Digital dan Inovasi Terhadap Kinerja Organisasi Pada Sekolah Yayasan Marsudirini Cabang Yogyakarta - Agatha Mayasari (Journal on Education, 2023)
This study examines the effect of digital transformation and innovation on organizational performance. Digital transformation and innovation are in the spotlight in the era of the Industrial Revolution 4.0 and Society 5.0 which have influenced and changed many things in the field of education. The existence of digital transformation and innovation that is carried out encourages skills and competencies to improve organizational performance which is one of the most important goals for the organization. This study uses a quantitative approach. The collecting data using a survey by distributing questionnaires. The respondents of this study were 83 teachers and employees from the Yayasan Marsudirini Cabang Yogyakarta at the elementary to middle education level. Testing the hypothesis of this study using Partial Least Square-Structural Equation Modeling (PLS-SEM) processed with SmartPLS. The results of the study show that digital transformation has a positive effect on organizational performance. Digital transformation has a positive effect on innovation. Innovation has a positive effect on organizational performance. The findings of this study prove that digital transformation and innovation have a positive influence on organizational performance which can encourage the Yayasan Marsudirini Cabang Yogyakarta schools to continue to strive for competitive advantage in providing educational services.